Bastard Culture!: How User Participation Transforms Cultural Production. - Garcia, D. Linda (Contemporary Sociology, 2012)
The article reviews the book "Bastard Culture!: How User Participation Transforms Cultural Production," by Mirko Tobias Schäfer.